Frontal osteomyelitis presenting as chronic preseptal abscess: an unusual scenario - Rawan Hosny; Abanoub Younan; Rania A. Ahmed (BMC Ophthalmology, 2025)
Abstract Preseptal cellulitis is characterized by local inflammation anterior to the orbital septum. This case is being reported to highlight a rare cause of a chronic form of preseptal inflammation: Frontal osteomyelitis. The patient initially presented with a chronic left upper lid swelling preceded by minor blunt trauma of four-month duration. Condition did not respond to medical treatment. Drainage of swelling was done and pus was sent for culture and sensitivity, results of which were negative. It rapidly recollected following drainage. Patient had no nasal complaints or constitutional manifestations. Computed tomography and magnetic resonance imaging diagnosed extent of sinus involvement and frontal osteomyelitis. Clindamycin therapy was given for four weeks following which the patient markedly improved.